2010
DOI: 10.1007/s12011-010-8643-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Selenium and Melatonin on Neuroprotection in Cerebral Ischemia in Rats

Abstract: The synergistic scavenger effects of selenium and melatonin collectively we called Se-Mel was studied on the prevention of neuronal injury induced by ischemia/reperfusion. Male Wistar rats were treated with sodium selenite (0.1 mg/kg, i.p.) and melatonin (10 mg/kg, i.p.) 30 min before the middle carotid artery occlusion (MCAO) and immediately after MCAO to male Wistar rats and was continued for 3 days once daily at the interval of 24 h. Behavioral activity (spontaneous motor activity and motor deficit) was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…It has been shown that selenium plays an important role in the continuation of the physiological functions of the nervous system (such as signal transduction and development) (10). Previous studies have shown that selenium has a neuroprotective role in various experimental pathologies, such as spinal cord injury, cerebral ischemia and neurotoxicity models (11)(12)(13)(14)(15). Similarly, in our previous study, selenium prevented neurotoxicity that was induced by cisplatin in a partial level (16).…”
Section: Introductionsupporting
confidence: 69%
“…Previous studies conducted with neurotoxic agents have demonstrated the neuroprotective effect of selenium on the central and peripheral nervous systems (8,(13)(14)(15)(16). However, this study was the first to demonstrate that selenium has a neuroprotective effect on peripheral nerve injury in rats.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies showed that using natural antioxidants supplements such as vitamin E (32), α-lipoic acid (33), flavonoids (34), oleanolic acid (35), selenium (36), vanadium, α-carotene, zinc, vitamin C (37, 38), aminoguanidine (39), lycopene (40) and natural phenolic compounds have protective effects on lipid peroxidation in diabetics and chronic disease (41). Several reports showed that selenium has neuroprotective effect and in cerebral ischemia and improves antioxidant capacity in vitro and in vivo in patients with coronary artery disease (42,43). The protective role of selenium administration against oxidized low density lipoprotein and antioxidant defense in diabetic rats was reported (44).…”
Section: Discussionmentioning
confidence: 99%
“…The human brain is characterised by a low (2,3%) content of Se [5]; however, it shows high priority for Se uptake in the case of its dietary deficiency. Even markedly decreased levels of Se in blood as observed in young rats on an Se-deficient 13-week diet, did not induce the significant changes in Se concentration in the brain [25].…”
Section: Selenium and Selenoproteins In Normal Brain Functionmentioning
confidence: 99%
“…Se is mainly consumed via food, which is a major source of organic Se at oxidation state II, which is better absorbed than the inorganic forms that are present in water. The total amount of Se in adult humans varies from between 10 to 20 mg and depends on many factors, such as place of living or health [3,5].…”
Section: Introductionmentioning
confidence: 99%